Tuberculous spondylitis: Macromorphological and radiological studies on a skeleton from the Late Iron Age monument of Nor Armavir, Armenia - Khudaverdyan, Anahit Yu.; Yengibaryan, Azat A.; Hmayakyan, Simon G.; Tiratsyan, Nvart G.; Hmayakyan, Margar S.; Vardanyan, Shota A.; Antonyan, Anna P.; Kocharyan, Vahan R. (Anthropological Review, 2024)
The skeleton in question derives from the Late Iron Age monument of Nor Armavir and was unearthed from burial No. 19. The deceased was buried in an unusual position. In this article, we characterize the pathological bony changes indicative of tuberculous spondylitis. The skeleton was subject to a detailed macroscopic investigation. Besides age at death estimation and sex determination, a careful palaeopathological evaluation was performed on the bone remains. In addition, volumetric (3D) computed tomography was carried out on four lumbar vertebrae (L2–5) to complement the macromorphology-based diagnosis.